Seroprevalence of Torque Teno Virus in hemodialysis and renal transplant patients in Australia: A cross‐sectional study. Issue 5 (27th July 2020) - Davis, Joshua S.; Chu, Ginger; Pathinayake, Prabuddhua; Jones, Denise; Giffard, Phil; Macera, Lisa; Choi, Peter; Bartlett, Nathan W.
Abstract: Introduction: Torque teno virus (TTV) is a non‐pathogenic anellovirus commonly found in the blood of human beings. Emerging data suggest that TTV viral load is proportional to the degree of immunosuppression, but its seroprevalence is unknown in Australia. We aimed to determine the seroprevalence of TTV in an Australian population of renal patients. Methods: We developed a real‐time PCR to measure TTV viral load, using the TaqMan platform and previously published primers and probes. Following ethics approval and informed consent, we collected blood from hemodialysis patients not receiving immunosuppression, and renal transplant patients. All patients were recruited from a single teaching hospital in New South Wales. Results: We enrolled 50 hemodialysis and 30 renal transplant patients. 56 (70%) were males, and the mean (sd) age was 61 (16) years. TTV was detectable in plasma of 40/50 (80%) of hemodialysis patients and 28/30 (93%) of transplant patients. The mean TTV viral load was higher in transplant patients than in dialysis patients (6.3 log versus 5.0 log copies/ml, P  = .001). Conclusions: Torque teno virus is prevalent in Australian renal patients and thus may be a useful novel marker to help tailor immunosuppressive therapy in renal transplant patients. Further work is needed to establish TTV seroprevalence in other regions and patient groups, and to investigate whether there is correlation with clinically important events (infection and rejection episodes) in longitudinal studies.